Implementasi Pemberian Izin Mendirikan Bangunan (Studi di Kota Bandar Lampung) - Agus Iskandar (Universitas Bandar Lampung (UBL), 2016)
To implement an integrated development through sustainable utilization of urban space, optimal, harmonious and balanced in accordance with the Act. To achieve these objectives, the mission and there are few attempts are made to create orderly development and urban development as the driving element of national development and is also in line with government policy. The problem in this paper is how the implementation of Spatial city of Bandar Lampung? Approach to problems that used juridical normative and empirical. Data was analyzed using qualitative analysis. The results showed the implementation of licensing erect the warehouse by the City Planning Office Bandar Lampung is still not optimal, this is very detrimental to the government because it can increase revenue (PAD). Suggestions should be aligned and balanced regulation that does not cause any harm either from the government or from the public in accordance with the city function optimally.